CONFLICT BETWEEN MILITARY ENGINEERING AND THE ROAD AND BRIDGE SERVICE FOR THE RECONSTRUCTION OF THE EL KANTARA BRIDGE IN CONSTANTINE - Mosbah Zoubir (International Journal of Innovative Technologies in Social Science, 2024)
The conflict which delayed the establishment of the El Kantara bridge (between military engineering and the bridges and roads service) was intended to communicate with the railway station and Philippeville on the coast. It made essential the role of Rue Nationale No. 3, between La Brèche, where commercial establishments, stores, warehouses, markets and the train station were concentrated. Also, the decision to reconstruct the El Kantara bridge was imminent. It was to be doubled by the railway network which was designed for strategic purposes by the French army (Shd, 1847). Therefore, the bridges and roads service had complete confidence in establishing the El Kantara bridge, following its experiences and skills carried out across other Algerian colonial cities. The reconstruction of the communication of the El Kantara bridge was the modern project for military engineering which allowed better exploitation of the colonial fabric of Constantine. This city was built on a rock made up of a large spur limited by the Rhumel ravines, crossed by the EI Kantara bridge which, having resumed service in 1863, was rebuilt in 1950. According to Berbrugger (1856), Constantine, without its numerous bridges spanning the abyss, is something that is difficult to imagine. For once, these gorges, the setting of so many tragic scenes over the centuries, had provided the people of Constantine with choice and completely unique entertainment. Not counting the very decorative but practically unusable natural arch, there are six bridges (Berbrugger, 1856).